The synthesis, property and reduction of high-nitrogen compound 3, 3′, 5, 5′-tetraazido-4, 4′-bis(1, 2, 4-triazole). (15th October 2016) - Lu, Feipeng; Wang, Engyu; Huang, Jinglun; Huang, Ming; Nie, Fude; Chen, Fu-Xue
Graphical abstract: High-nitrogen compound 3, 3′, 5, 5′-tetraazido-4, 4′-bis(1, 2, 4-triazole) (TABT, 83.99% N) was synthesized from the reaction of sodium azide and 3, 3′, 5, 5′-tetrabromo-4, 4′-bis(1, 2, 4-triazole) (TBBT) in DMSO, which was prepared by a bromination reaction of 4, 4′-bis(1, 2, 4-triazole) (BTz). Abstract: High-nitrogen compound, 3, 3′, 5, 5′-tetraazido-4, 4′-bis(1, 2, 4-triazole) (TABT, 83.99% N), is synthesized from sodium azide and 3, 3′, 5, 5′-tetrabromo-4, 4′-bis(1, 2, 4-triazole) (TBBT) which is prepared by the bromination of 4, 4′-bis(1, 2, 4-triazole) (BTz). It is fully characterized by IR, HRMS, NMR, and single crystal X-ray diffraction showing two triazole rings of TABT perpendicular to each other. DSC and TGA are employed to study TABT's thermal stability with a decomposition temperature at 125.39 °C (onset). The calculated detonation heat of TABT and the predicted detonation velocity are 6449 kJ·kg −1 and 8649 m·s −1, respectively. The reduction of TABT with hydrogen and Pd/C gave the stabilized 3, 3′, 5, 5′-tetra(t-butyloxycarbamido)-4, 4′-bis(1, 2, 4-triazole) (11 ) in the presence of (Boc)2 O, providing an alternative path to the high energy density material (HDEM) TNBT [3, 3′, 5, 5′-tetranitro-4, 4′-bis(1, 2, 4-triazole)].